1996
DOI: 10.1002/(sici)1099-1379(199601)17:1<5::aid-job734>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Attraction in organizations: A model of workplace romance

Abstract: Antecedents and consequences of participating in a romantic relationship in the workplace are critically examined. These factors are derived from social-psychological theories of interpersonal attraction, romantic attraction, love, emotion, and social exchange, as well as from previous research addressing romance in the workplace. The antecedent factors explain the processes by which romantic relationships develop between two members of the same organization, and the consequent factors highlight both the benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
210
0
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(223 citation statements)
references
References 79 publications
(103 reference statements)
8
210
0
2
Order By: Relevance
“…Romantic relationships at the workplace are consensual and mutually welcomed (Clarke, 2006). Ariani (2011) explained that workplace romances are characterized by desiring to be with the other person and feelings of emotional and physical attraction, which may lead to a sharing of personal information, mutual caring and respect, and quite likely sexual behavior such as touching, kissing and hugging, and sexual intercourse (Pierce et al, 1996). Lickey (2009) described workplace romance as working together allows people to get to know each other and as familiarity grows, workplace romances may be more likely to occur.…”
Section: Romance At Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Romantic relationships at the workplace are consensual and mutually welcomed (Clarke, 2006). Ariani (2011) explained that workplace romances are characterized by desiring to be with the other person and feelings of emotional and physical attraction, which may lead to a sharing of personal information, mutual caring and respect, and quite likely sexual behavior such as touching, kissing and hugging, and sexual intercourse (Pierce et al, 1996). Lickey (2009) described workplace romance as working together allows people to get to know each other and as familiarity grows, workplace romances may be more likely to occur.…”
Section: Romance At Workmentioning
confidence: 99%
“…Levels of productivity may be lower at the start of the relationship as large amounts of time and energy are invested in it. Once the initial excitement of the new romance lessens, productivity tends to rise steadily (Pierce et al, 1996). Those who show a love motive avoid the negative consequences of inadequate performance by demonstrating increased effort in order to impress their supervisors.…”
Section: Romance At Workmentioning
confidence: 99%
“…Since people are more likely to be sexually attracted to people who share similar attitudes and interests, the workplace is a suitable setting to start a love relation (Smith, Becker, Byrne, & Przybyla, 1993). "Working closely with others appears to foster interpersonal attraction" (Maniero, 1986, p. 752), and when employees work overtime and attend out-of-town conferences together, they are naturally more inclined to socialize with each other (Pierce, Byrne, & Aguinis, 1996). Gutek, Cohen, and Konrad (1990) found that non-work-related sexualized behavior such as sexual jokes, comments, and innuendo had no significant effect on employees' self-reports of romances at work, but did influence their tendency to others' romances.…”
Section: The Context Of Workplace Romancesmentioning
confidence: 99%
“…Collaboration increases the likelihood of having a fair or falling in love at work (Karl & Sutton, 2000;Pierce, Byrne, & Aguinis, 1996). It can lead to informal interaction and to feelings of affection.…”
mentioning
confidence: 99%